Molecular Interplays Between Cell Invasion and Radioresistance That Lead to Poor Prognosis in Head-Neck Cancer - You, Guo-Rung; Chang, Joseph T.; Li, Yan-Liang; Chen, Yin-Ju; Huang, Yu-Chen; Fan, Kang-Hsing; Chen, Yen-Chao; Kang, Chung-Jan; Cheng, Ann-Joy (Frontiers in Oncology, 2021)
Background: Cancer metastasis and recurrence after radiotherapy are the significant causes of poor prognosis in head-neck cancer (HNC). Clinically, it is commonly found that patients with either condition may accompany the outcome of the other. We hypothesized that HNC cells might exhibit a cross-phenotypic attribute between cell invasion and radioresistance. To discover effective biomarkers for the intervention of aggressive cancer at one time, the potential molecules that interplay between these two phenotypes were investigated. Materials and Methods: Three isogenic HNC cell sublines with high invasion or radioresistance properties were established. Transcriptomic and bioinformatic methods were used to globally assess the phenotypic-specific genes, functional pathways, and co-regulatory hub molecules. The associations of gene expressions with patient survival were analyzed by Kaplan-Meier plotter, a web-based tool, using the HNSCC dataset (n=500). The molecular and cellular techniques, including RT-qPCR, flow cytometry, cell invasion assay, and clonogenic survival assay, were applied. Results: The phenotypic crosstalk between cell invasion and radioresistance was validated, as shown by the existence of mutual properties in each HNC subline. A total of 695 genes was identified in associations with these two phenotypes, including 349 upregulated and 346 downregulated in HNC cells. The focal adhesion mechanism showed the most significant pathway to co-regulate these functions. In the analysis of 20 up-regulatory genes, a general portrait of correlative expression was found between these phenotypic cells (r=0.513, p=0.021), and nine molecules exhibited significant associations with poor prognosis in HNC patients (HR>1, p<0.050). Three hub genes were identified (ITGA6, TGFB1, and NDRG1) that represented a signature of interplayed molecules contributing to cell invasion, radioresistance and leading to poor prognosis. The ITGA6 was demonstrated as a prominent biomarker. The expression of ITGA6 correlated with the levels of several extracellular and apoptotic/anti-apoptotic molecules. Functionally, silencing ITGA6 suppressed cell migration, invasion, and attenuated radioresistance in HNC cells. Conclusions: A panel of interplay molecules was identified that contribute to cell invasion and radioresistance, leading to poor prognosis. These panel molecules, such as ITGA6, may serve as predictive markers of radioresistance, prognostic markers of metastasis, and molecular therapeutic targets for refractory HNC.